Procedural Planning System for Appropriate Land Use Configuration: Anticipating Tsunami in Glagah Village, Yogyakarta - Wahyuni, Lina; Rukhsana (Department of Geography Education, University of Jember, Indonesia, 2024)
The establishment of Kulon Progo as a strategic zone must consider the threat of coastal disasters besides aspiring economic growth and development. By employing Unmanned Aerial Vehicles for data acquisition, this research modeled flood inundation and developed theoretical contributions on tsunami hazard, vulnerability, capacity, and risk, as well as a procedural planning system for reconfiguring land use that emphasized the mitigation aspects. This study found that the tsunami hazard index in Glagah Village was in a low category, dominated by vacant land and sandy land, accounting for up to 25.38% of the total area. Besides, vulnerability and risk in Glagah Village were mostly in a moderate index, while its capacity was categorized as high since the village already had an evacuation route, a notable tsunami early warning system, and was equipped with safety gear. By combining the index values for hazard, vulnerability, and capacity, the tsunami disaster risk in Glagah Village was categorized as moderate. Spatial planning in Glagah Village recommended that the main facilities related to community activities, such as transportation and housing, be located in areas not exposed to the tsunami. This plan allows everyone to evacuate themselves while being reinforced by a security warning system that stays on alert. Furthermore, detailed spatial maps are expected to be useful as instruments for tsunami disaster mitigation at the pre-disaster stage by recommending better land use configurations.